Case Report: Novel Compound Heterozygotic Variants in PPP2R3C Gene Causing Syndromic 46, XY Gonadal Dysgenesis and Literature Review - Zhang, Wei; Mao, Jiangfeng; Wang, Xi; Sun, Bang; Zhao, Zhiyuan; Zhang, Xiaoxia; Nie, Min; Wu, Xueyan (Frontiers in Genetics, 2022)
Purpose: Patients with syndromic 46, XY disorders of sex development (DSD) are characterized by gonadal and phenotypic genders inconsistent with their chromosomal sexes, as well as abnormalities of multiple extra-gonadal organs. They were caused by mutations in specific genes, which express in the affected organs and regulate their development, and over fourteen genes have been identified. In this study, we aimed to determine the underlying cause of a patient with syndromic 46, XY DSD and review the clinical presentations and genetic findings of all reported similar cases. Methods: Whole-exome sequencing (WES) was performed to find the gene mutation of the patient. In-silico tools were used to analyzed the pathogenicity of the variants. Reports of cases with similar clinical features and involved genes were summarized by searching through PubMed/Medline using keywords “PPP2R3C” or “G5PR” and “disorders of sex development”. Results: Compound heterozygous variants (p.F229del/p.G417E) in PPP2R3C were identified from the 24-year-old female by WES and verified by Sanger sequencing. The patient presents complete testicular dysgenesis, low birth weight, facial deformity, cubitus valgus, decreasing number of CD19+ B lymphocytes and CD4+ T lymphocytes. A total of 13 46, XY DSD cases with four homozygous PPP2R3C mutations (p.Leu103Pro, p.Leu193Ser, p.Phe350Ser and p.Ser216-Tyr218dup) have been reported previously, and their clinical manifestations are roughly similar to those of our patient. Conclusion: Novel compound heterozygous variants in PPP2R3C cause specific syndromic 46, XY gonadal dysgenesis, which broadened the pathogenic variants spectrum of PPP2R3C. The typical phenotype of PPP2R3C mutation is complete 46, XY gonadal dysgenesis with multiple extragonadal anomalies, including facial deformities, skeletal system abnormalities, muscle abnormalities, impaired nervous system, impaired hearing and vision, heart and kidney anomalies, gastrointestinal dysfunction.